Outcomes After Transcervical Thymectomy for Ocular Myasthenia Gravis: A Retrospective Cohort Study With Inverse Probability Weighting. Issue 1 (March 2020) - Hamedani, Ali G.; Pistilli, Maxwell; Singhal, Sunil; Shindler, Kenneth S.; Avery, Robert A.; Tamhankar, Madhura A.; Liu, Grant T.
Abstract : Background: The benefit of thymectomy in reducing requirement for corticosteroids, symptom severity, need for immunosuppression, and hospitalization rates in patients with seropositive generalized myasthenia has recently been established. It is unclear whether this benefit applies to patients with myasthenia and purely ocular manifestations (ocular myasthenia gravis [OMG]). Methods: We conducted a retrospective single-center cohort study of patients with OMG. Patients were included if their diagnosis was confirmed by acetylcholine receptor or muscle-specific kinase antibodies, abnormal electrophysiology, or a positive edrophonium test and at least 1 year of clinical follow-up. At each visit, the presence and severity of ocular and generalized symptoms was ascertained using a 4-point scale. Prednisone dose, steroid-sparing agent use, and need for intravenous immunoglobulin or plasmapheresis were recorded. The effect of thymectomy on time-weighted prednisone dose and symptom severity score was assessed using linear regression models. To adjust for nonrandomization of thymectomy, we used inverse probability weighting using a propensity score model derived from the prethymectomy observation period for thymectomy patients and a 6-month lead-in period for nonthymectomy patients that incorporated age, sex, acetylcholine receptor antibody seropositivity, disease severity (as defined by both symptom severity and treatment requirement), and treating physician preferences. Results: Eighty-two patients (30 with thymectomy and 52 nonthymectomy) were included. In unadjusted analyses, time-weighted daily prednisone dose was 2.9 mg higher with thymectomy compared with nonthymectomy (95% CI: 0.2–5.7), but after inverse probability weighting, this was no longer statistically significant (difference = 1.7 mg, 95% CI: −0.8 to 4.2). There was no statistically significant difference in symptom severity score (adjusted difference = 0.35, 95% CI: −0.02 to 0.72) or risk of generalization ( P = 0.22). Conclusions: In this retrospective study that used statistical techniques to account for nonrandomization, no significant differences in prednisone dose or symptom severity after thymectomy in ocular myasthenia were demonstrated.